THE INVOLVEMENT OF TECHNOLOGY IN ONLINE GRAMMAR LEARNING DURING COVID-19 PANDEMIC - Robbi Nurdin Hidayat (UC Journal: ELT, Linguistics and Literature Journal, 2021)
Covid-19 pandemic has caused a lot of changes in the field of English learning. In addition, this situation has led to a new method towards learning English specifically on grammar skills. The shift from face to face to online learning method brings about major involvements of technology in the learning process. This paper gives overviews on some technology-based tools used in learning English grammar skills specifically. The purpose of this paper is to elaborate the complicity of technology in learning English grammar. Furthermore, the effects of the new method towards the grammar learning mechanisms are also studied. Literature reviews are used as a method to explain the involvement of technology-based tools in the learning. This paper also includes several suggestions on the effective uses of technology in learning English grammar.